A rare case of post-ictal diffuse alveolar hemorrhage due to seizures (Indian Journal of Case Reports, 2024)
Diffuse alveolar hemorrhage is persistent or recurrent pulmonary hemorrhage that occurs due to a variety of causes. Here, we present the case of a 15-year-old male child who presented with chief complaints of involuntary jerking movements of the entire body in the morning followed by coughing out a massive amount of blood. At presentation, the patient’s blood glucose level was high. Bronchoscopy revealed bleeding in the middle and lower lobes of both lungs. Computed tomography (CT) brain was suggestive of cerebral edema and the CT chest was suggestive of diffuse opacities in bilateral lung fields. The patient was started on corticosteroids, antiplatelet drugs, antiepileptics, insulin, and oxygen inhalation which helped the patient to recover and was discharged in a week’s time.